Eco-efficiency assessment of the sugarcane production system using a four-step integrated life cycle and data envelopment analysis. Issue 1 (31st December 2023) - Powar, R. V.; Powar, T. R.; Bandgar, P. S.; Patil, S. B.
ABSTRACT: Sugarcane is an energy-intensive crop that requires a large amount of input resources. The production and usage of all these resources are liberated huge amounts of GHGs (Greenhouse gases). Therefore, to address these issues, the objectives of the study were decided to assess the eco-efficiency of the sugarcane crop, quantify the GHG emissions from sugarcane farms, and investigate ways to reduce the GHG emissions from sugarcane farming. LCA+DEA approach was used to evaluate the eco-efficiency of the sugarcane production system using a four-step method. The output-oriented BCC model was selected for benchmarking and estimating the efficiency score of DMUs. The average sugarcane production and carbon emissions of study area were found to be 148.75 t ha −1 and 3234.83 kg CO2eq ha −1, respectively. Nitrogen fertilizers contributed highest share in carbon emissions (50.15%), followed by P2 O5 (26.98%), diesel (11.72%), K2 O5 (6.94%), micro nutrients (2.24%), total machinery (1.14%), and biocides (0.82%), respectively. The average current GHG emissions from the input resources were found to be 1590, 929, 267, 445, and 3231 Kg CO2eq ha −1 for N, P2 O5, K2 O, diesel, and total carbon footprint (CF), respectively, and targeted GHG emission from input resources for better performance were 211, 336, 621, 165, and 1333 Kg CO2eq ha −1, respectively. The GHG emission contribution of N, and P2 O5 must be reduced by 86.72% and 63.83%, respectively, to meet the GHG emission target set by the efficient DMUs and additional K2 O (57%) might be used for the farming operations. Furthermore, the diesel consumption of agricultural machinery is not possible to reduce because improved mechanization practices in sugarcane farming will increase the diesel consumption.